How does the first index mode of birth in public or private hospitals predict subsequent births? A 16-year Australian population-based linked data study - Soo Downe; Hannah G Dahlen; Ank de Jonge; Lilian Peters; Michiel de Boer (BMJ Open)
Objectives In this descriptive study, we aimed to assess how the index mode of birth and subsequent birth modes vary over time for public and private hospital maternity care funding models. The second aim was to determine to what extent the index mode of birth predicts subsequent birth modes in general and whether this differs in public versus private hospital maternity care funding models. With our aim, we have an innovative approach, specifically the women’s life course approach, which is hypothesis-generating and can be assessed in future studies.Design, setting and participants New South Wales population-linked data of low-risk women were analysed (2001–2016). Demographics and public/private care were recorded. Modes of the index birth and subsequent modes of second and third births (ie, spontaneous vaginal, instrumental vaginal elective/emergency caesarean birth) were registered. For those with 2 births and 3 births, 16 and 64 subsequent births patterns were created.Primary and secondary outcome measures Trend of index modes of birth and subsequent modes of birth over time and the prediction of subsequent birth modes based on the index birth. These outcomes were stratified for the initial maternity care funding model.Results In total, 172 041 low-risk nulliparous women were included in the initial cohort, 54.1% had a spontaneous index vaginal birth and 71% had their index birth in public hospitals. During the study period, 131 675 women had 2 births and 44 677 of these women had 3 births, respectively. Among women birthing in public hospitals, higher proportions of index and subsequent vaginal births were observed than in private hospitals, with fewer instrumental vaginal births and caesarean sections. Large differences were observed for birth patterns: vaginal-vaginal (public 55.8% vs private 36.8%) and vaginal-vaginal-vaginal (public 57.2% vs private 38.8%). Women with an index spontaneous vaginal birth showed a high probability (91.3%) of subsequent spontaneous vaginal births. When stratified by maternity care funding model, the probabilities were similar: 91.6% in public hospitals and 90.2% in private hospitals.Conclusions Our study of low-risk Australian women (2001–2011) found that those giving birth in public hospitals had higher proportions of spontaneous vaginal births compared with private hospitals, where caesarean sections were more common. Women with an index spontaneous vaginal birth had a very high probability to have subsequent vaginal births. These findings suggest that index mode of birth may be a predictor for subsequent modes of birth.